DIFFERENTIATED LEARNING STRATEGIES TO DEVELOP CRITICAL THINKING SKILLS IN EARLY CHILDHOOD - Rocmah, Luluk Iffatur; Rezania, Vanda; Wulandari, Ria (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to explore and describe the implementation of differentiated learning strategies in early childhood education and their impact on the development of critical thinking skills at TK ABA Bebekan. Method: Utilizing a qualitative descriptive approach, data were collected over five weeks through classroom observations, teacher interviews, and documentation analysis. The study focused on class B, where differentiated strategies were implemented based on children's learning styles and interests. Results: The findings indicate that the teacher employed three forms of differentiation—process, content, and product. Children were more engaged, demonstrated increased curiosity, and exhibited critical thinking behaviors such as asking questions, reasoning, making decisions, and solving problems. Specifically, 12 out of 15 children actively questioned phenomena, and 13 made independent choices during learning. Novelty: This study contributes to the limited literature on early childhood differentiated instruction in Indonesia by highlighting its practical application in enhancing critical thinking, particularly through individualized learning activities that respect children’s developmental uniqueness.